In vitro Propagation of Bitter Gourd (Momordica charantia L.) from Nodal and Root Segments (Plant Tissue Culture and Biotechnology, 2010)
Explants of nodal and root segments of bitter gourd were cultured on MS supplemented with various concentrations of BAP in combination with either 2,4-D or NAA. Nodal segments produced the highest percentage (93.75) of callus in MS supplemented with 1.0 mg/l 2,4-D and 1.0 mg/l BAP whereas, root segments produced the highest (85.00%) callus in 0.6 mg/l NAA and 2.5 mg/l BAP combination. A combination of 1.0 mg/l 2,4-D and 1.0 mg/l BAP exhibited 75.00% shoot regeneration from nodal segments. The highest shoot length (5.15 cm) was recorded with 2.5 mg/l BAP and 0.2 mg/l IAA from nodal segments. No sign of regeneration of shoot was found from root segments in any of the combinations. However, some combinations produced only roots.  Key words: In vitro propagation, bitter gourd, nodal segments, Root segments D.O.I. 10.3329/ptcb.v19i1.4916 Plant Tissue Cult. & Biotech. 19(1): 45-52, 2009 (June)